Short Communication: Macropropagation – An important tool for conservation of North Sumatran endangered tree species, Dryobalanops aromatica - ARIDA SUSILOWATI; CUT RIZLANI KHOLIBRINA; HENTI HENDALASTUTI RACHMAT; DENI ELFIATI; ASWANDI .; ILLA MASYITAH RAENI (Society for Indonesian Biodiversity, 2018)
Susilowati A, Kholibrina CR, Rachmat HH, Elfiati D, Aswandi, Raeni IM. 2018. Short Communication: Macropropagation -An important tool for conservation of North Sumatran endangered tree species, Dryobalanops aromatica. Biodiversitas 19: 1672-1675.Dryobalanops aromatica or locally known as kapur is a tree producing borneol used for pharmaceutical purposes. Due to illegalharvesting for wood and borneol, depauperate population with low and rare reproductive mother trees and land conversion to oil palmplantation, its population decreases every year. Ex situ and in situ conservation efforts are needed to prevent this species from extinction.One of the ex situ conservation efforts that can be done is propagating this species vegetatively with shoot cuttings. Shoot cutting istechnically simple and inexpensive method to produce new planting stock for further purposes such as production and conservation.This method has also been successfully used for the propagation of endangered and highly economically valuable species. Despite manyapplications of shoot cutting for clonal forestry, there was still lack of information about the successfulness of this method forDryobalanops aromatica. Therefore the objective of this research was to get data about the successfulness of kapur cuttings usingdifferent media and growth regulator treatment. A factorial experiment using a Completely Randomized Design with two factors wasconducted for this research. The first factor was cutting media, consisting of three types, namely (i) sand, (ii) combination of sand andsoil, and 3) combination of sand, soil and rice husk. The second factor was plant growth regulator (PGR), consisting of two levels,namely (i) without PGR addition and (ii) with PGR addition. The parameters observed were survival percentage, rooting percentage,number of primary and secondary roots, length of primary and secondary roots and adventitious root formation. Results showed thatrooting percentage of cutting using this technique varied from 30 to 60% and thus this technique was prospective to be developed as atool for propagating kapur trees. Adventitious roots originated from the wounded area near the cambium which was later followed bythe formation of callus and root primordia.